The diversity and traditional use of home garden plants near Kerinci Seblat National Park, Indonesia - ADI BEJO SUWARDI; ZIDNI ILMAN NAVIA; ALBIAN MUBARAK; RODIYATUL RAHMAT; PANJI CHRISTY; SARA GUSTIA WIBOWO; HERI IRAWAN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Suwardi AB, Navia ZI, Mubarak A, Rahmat R, Cristy P, Wibowo SG, Irawan H. 2024. The diversity and traditional use of home garden plants near Kerinci Seblat National Park, Indonesia. Biodiversitas 25: 3284-3299. Home gardens are traditional agroforestry systems that improve plant diversity and ecosystem services while also having a direct and beneficial effect on human well-being. Each plant species in a home garden provides a variety of ecosystem services, which are linked to specific ecological functions and social drives. Although home gardens are biodiversity hotspots and have recently been identified as essential to tropical biodiversity conservation, the benefits of ecosystem services offered by home gardens are frequently undervalued. This study aims to analyze the diversity, usage, and traditional knowledge of home garden plants among the local communities living near Kerinci Seblat National Park, Indonesia. This study was carried out in four villages from two districts of Bengkulu Province, Indonesia, i.e. Lebong and Rejang Lebong. Field surveys, plant collections, and interviews with local communities were used in this study. Interviews were conducted with 120 informants (30 in each village) selected at random. A total of 218 plant species belonging to 67 families associated with 12 use categories were recorded in the study area. Capsicum frutescens, Musa x paradisiaca, and Mangifera indica are frequently discovered in home gardens. The most diverse categories of plant use in home gardens encompass food, medicine, and ornament, utilizing various parts such as rhizomes, leaves, flowers, and fruits. Home gardens, with their diverse plant species, are considered to have a significant role in household livelihoods, protecting plant genetic resources, and biodiversity conservation.